Seasonal abundance and diversity of aquatic insects in rivers in Gunung Jerai Forest Reserve, Malaysia - Suhaila, A.H.; Che Salmah, M.R.; Nurul Huda, A. (Universiti Kebangsaan Malaysia, 2014)
Seasonal changes in Ephemeroptera, Plecoptera and Trichoptera (EPT) community was studied at rivers in Gunung Jerai Forest Reserve, Kedah, Malaysia. The rivers were visited monthly from September 2007 to August 2008 to sample aquatic insects using D-pond nets. More EPT were found in the wet season (10664 individuals) compared with the dry season (6599 individuals). In all rivers, ephemeropteran populations was highest during the wet season (z=-2.465, p=0.014). Meanwhile, the plecopteran population was low and almost constant throughout seasons in all rivers (z=-2.280, p=0.023). Trichopterans exhibited the highest peak of abundance in the dry season (z=-6.096, p=0.00). Concomitantly, higher diversity was recorded in the dry season (29 taxa) compared with 25 taxa recorded in wet season from all rivers. Tupah River had the most diverse EPT assemblage during the dry season. In wet season, the abundance of ephemeropterans genera such as Baetis, Platybaetis, Campsoneuria and Thalerosphyrus increased tremendously especially in Teroi River.